A Randomized Clinical Trial of Primary Care Brief Mindfulness Training for Veterans With PTSD. Issue 3 (27th November 2015) - Possemato, Kyle; Bergen‐Cico, Dessa; Treatman, Scott; Allen, Christy; Wade, Michael; Pigeon, Wilfred
Abstract : Objectives: Primary care (PC) patients typically do not receive adequate posttraumatic stress disorder (PTSD) treatment. This study tested if a brief mindfulness training (BMT) offered in PC can decrease PTSD severity. Method: VA PC patients with PTSD ( N = 62) were recruited for a randomized clinical trial comparing PCBMT with PC treatment as usual. PCBMT is a 4‐session program adapted from mindfulness‐based stress reduction. Results: PTSD severity decreased in both conditions, although PCBMT completers reported significantly larger decreases in PTSD and depression from pre‐ to posttreatment and maintained gains at the 8‐week follow‐up compared with the control group. Exploratory analyses revealed that the describing, nonjudging, and acting with awareness facets of mindfulness may account for decreases in PTSD. Conclusion: Our data support preliminary efficacy of BMT for Veterans with PTSD. Whether PCBMT facilitates engagement into, or improves outcomes of, full‐length empirically supported treatment for PTSD remains to be evaluated.